Recovery Pattern of High-Frequency Acceleration Vestibulo-Ocular Reflex in Unilateral Vestibular Neuritis: A Preliminary Study - Fu, Wei; He, Feng; Wei, Dong; Bai, Ya; Shi, Ying; Wang, Xiaoming; Han, Junliang (Frontiers in Neurology, 2019)
Objective: To explore the recovery pattern of the high-frequency acceleration vestibulo-ocular reflex (VOR) function in unilateral vestibular neuritis (UVN). Methods: Forty-seven consecutive patients with UVN were recruited within 10 days of symptom onset for this study. The high-frequency acceleration horizontal VOR function was assessed using the video head impulse test (vHIT). Patients returned for follow-up evaluation at 6 months after the onset of symptoms. According to the dizziness handicap inventory questionnaire (DHI), the patients were classified into the normal to mild dizziness group (DHI score ≤30) and moderate to severe dizziness group (DHI score >30) at the follow-up. All the obtained horizontal vHIT gains and corrective saccades parameters were analyzed. Results: vHIT results showed a significantly horizontal VOR gain recovery in UVN patients at the follow-up on the lesion side (p < 0.01). A significantly reduction in the occurrence of corrective saccades (overt and covert) and velocity of corrective saccades (overt and covert) were observed at the follow-up (p < 0.05). At the follow-up, the normal to mild dizziness group (DHI score ≤30) had a significantly higher normal rate of VOR gain, the mean vHIT gains and occurrence of isolated covert saccades (P < 0.05). Furthermore, the occurrence of mixed saccades and the mean velocity of covert saccades were significantly lower in normal to mild dizziness group (P < 0.05). Conclusion: Apart from the recovery of the VOR gain, recovery pattern of corrective saccades can play a key role in vestibular compensate.